Treatment of sepsis-induced acute kidney injury in the ICU: the therapeutic targets do not seem to be established yet - Quenot, Jean-Pierre; Dargent, Auguste; Large, Audrey; Roudaut, Jean-Baptiste; Andreu, Pascal; Barbar, Saber (Annals of Translational Medicine, 2019)
Acute kidney injury (AKI) is a frequent complication in patients hospitalized in the intensive care unit (ICU) for sepsis (1,2). It is associated with long-term sequelae such as chronic kidney disease (3) and high mortality (2,4), especially in case of severe AKI associated with septic shock.